2020
DOI: 10.1186/s12974-019-1616-z
|View full text |Cite
|
Sign up to set email alerts
|

The spinal microglial IL-10/β-endorphin pathway accounts for cinobufagin-induced mechanical antiallodynia in bone cancer pain following activation of α7-nicotinic acetylcholine receptors

Abstract: Background: Cinobufagin is the major bufadienolide of Bufonis venenum (Chansu), which has been traditionally used for the treatment of chronic pain especially cancer pain. The current study aimed to evaluate its antinociceptive effects in bone cancer pain and explore the underlying mechanisms. Methods: Rat bone cancer model was used in this study. The withdrawal threshold evoked by stimulation of the hindpaw was determined using a 2290 CE electrical von Frey hair. The β-endorphin and IL-10 levels were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 91 publications
1
26
0
Order By: Relevance
“…More directly, cultured microglial cells coexpressed IL-10 and α7 nAChRs and cynandione A incubation stimulated expression of IL-10 but not α7 nAChRs, which was totally blocked by methyllycaconitine. It was also recently reported that the specific α7 nAChR agonist PHA-543163 stimulated methyllycaconitine-reversible IL-10/β-endorphin expression in cultured microglial cells ( Apryani et al, 2020 ). These results together suggest that cynandione A induces spinal microglial expression of IL-10/β-endorphin and produces antinociception through α7 nAChR activation.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…More directly, cultured microglial cells coexpressed IL-10 and α7 nAChRs and cynandione A incubation stimulated expression of IL-10 but not α7 nAChRs, which was totally blocked by methyllycaconitine. It was also recently reported that the specific α7 nAChR agonist PHA-543163 stimulated methyllycaconitine-reversible IL-10/β-endorphin expression in cultured microglial cells ( Apryani et al, 2020 ). These results together suggest that cynandione A induces spinal microglial expression of IL-10/β-endorphin and produces antinociception through α7 nAChR activation.…”
Section: Discussionmentioning
confidence: 91%
“…However, this conclusion is compromised by lacking elucidated interactions of cynandione A with α7 nAChRs at the molecular level. Particularly, our previous studies also revealed that the spinal microglial IL-10/β-endorphin pathway in bone cancer pain and neuropathic pain mediated the α7 nAChR agonists PHA-543613-, cinobufagin- and lemairamin-induced antinociception, although their chemical structures were different ( Apryani et al, 2020 ; Wang et al, 2020 ). Further studies are needed to assess the activities of cynandione A, as well as PHA-543613, cinobufagin, and lemairamin, on α7 nAChRs by using radioligand analysis, electrophysiology, or calcium imaging FLIPR assays.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been extensively reported that 7 nAChRs are colocalized on microglial cells as determined by qRT-PCR, western blot, immuno uorescent, and immunohistochemistry analyses and their activation is associated with antinociception and neuroprotection [29,[53][54][55]. More speci cally, it was recently identi ed that the spinal microglial IL-10/β-endorphin pathway mediated the α7 nAChR agonists PHA-543613-, cinobufaginand lemairamin-induced antinociception in bone cancer pain and neuropathic pain [31,32]. Our current study demonstrated that methyllycaconitine signi cantly blocked cynandione A-induced mechanical antiallodynia in neuroapthic rats, and the expression of IL-10 and β-endorphin in the spinal cords and cultured primary microglial cells.…”
Section: Cynandione a Stimulated Il-10 And β-Endorphin Expression In mentioning
confidence: 99%
“…It was suggested that activation of α7 nAChRs blocked neuropathic pain through promoting expression of the antiin ammatory cytokine IL-10 and inhibiting the expression of proin ammatory cytokines such as IL-1β, IL-6, and TNF-α [29,30]. It was also recently revealed that activation of α7 nAChRs produced antinociception in rat models of neuropathic pain and bone cancer pain via spinal microglial pathway of IL-10 and β-endorphin [31,32].…”
Section: Introductionmentioning
confidence: 99%